State's fiscal management and regional equity - Rao, M.Govinda. (ed.) (New Delhi, 2009)
The states in India have a predominant role in advancing human development and a co-equal role with the central government in the provision of economic services. The condition of states' fiscal health, therefore, determines both the nature and quality of economic growth in the country. With contributions from leading fiscal experts, this volume presents an overview of the challenges of fiscal management faced by states and the national challenge of regional fiscal equity. It addresses a variety of issues related to state finances, regional developmental policies, and the design and implementation of intergovernmental transfers, including the National Rural Employment Guarantee Act. Using the latest data on federal-state finances, the essays analyse the impact of fiscal policies and institutions on inter-state disparities. Ironically, the states that are rich in resources are the least developed- while their resources are exploited for national benefit, they themselves have lagged behind due to inadequate compensation. The volume argues that realizing the developmental potential of the country will depend upon the fiscal management by the centre to create a common market and enable a level playing field for lagging states. Equally important is the latter's own efforts at raising revenues and efficiently managing resources. Addressing important policy concerns for ensuring sustainable and inclusive growth, this volume is an important contribution in the area of federal finance.
Keywords: Fiscal change-India